" A Comparative Study between Bone Age and Chronological Age in Down Syndrome Patients using Lateral Cephalometric Radiographs and Hand-Wrist X-Ray " (Journal of Hama University, 2021)
Assessment of skeletal maturity and growth in patients with Down syndrome using Lateral cephalometric and hand and wrist radiographs.The study was conducted on a sample consisting of (48) patients distributed as follows:Group 1: Down syndrome patients, a number of 24 patients, aged (8-14) years.Group 2: normal patients, a number of 24 patients, aged (8-14) years.Lateral Cephalometrics were performed for all the subjects of the research sample using the (Carestream , CS 9300,France) device, as well as the X-rays of the hand and wrist were performed using the (LISTEM, CST-21HF II, korea ) device, and then many measurements(cervical lengths -cervical concavity-…) were made using the computer by the (CS Imaging Software, 7.0.23.0.d2) program and the T Test was performed for independent samples using the statistical program SPSS 20 when comparing the normal patients’ group with Down’s patients’ group that comprised the study sample.The results showed that there were no statistically significant differences between the two groups of normal patients and patients with Down syndrome in terms of the degree of bone growth and development at the level of both the cervical spine(from C2 to C6) and the bones of the hand and wrist.There was no statistically significant differences in terms of the increase in the length of the cervical vertebrae, as well as the absence of statistically significant differences in the degree of growth and development of the bones of the hand and wrist between the group of patients with Down syndrome and the group of normal patients in the study sample.